2010
DOI: 10.1111/j.1524-4725.2010.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment of Melomental Fold Rhytides with Cross-Linked Hyaluronic Acid Combined with OnabotulinumtoxinA and Cross-Linked Hyaluronic Acid Alone

Abstract: Cross-linked HA and onabotulinumtoxinA combination therapy to melomental fold rhytides may provide better overall aesthetic results and longer duration of aesthetic improvement than cross-linked HA monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Botulinum toxin injection, administered with or prior to dermal filler, appears to also significantly improve the aesthetic result of HA filler treatment of the nasolabial fold (NLF). Two studies, by Custis et al and Carruthers and Carruthers, found that concurrent botulinium toxin and HA dermal filler treatment appeared to prolong the duration of correction by 6.5 and 14 weeks, respectively, compared to the treatment of HA dermal filler alone 6,10,11…”
Section: Methodsmentioning
confidence: 99%
“…Botulinum toxin injection, administered with or prior to dermal filler, appears to also significantly improve the aesthetic result of HA filler treatment of the nasolabial fold (NLF). Two studies, by Custis et al and Carruthers and Carruthers, found that concurrent botulinium toxin and HA dermal filler treatment appeared to prolong the duration of correction by 6.5 and 14 weeks, respectively, compared to the treatment of HA dermal filler alone 6,10,11…”
Section: Methodsmentioning
confidence: 99%
“…6 Recent clinical trials demonstrated the efficacy and safety of combination therapy for lower facial rejuvenation, with better results than either modality alone. 56,57 Although there are limited data for treatment of the lower face and neck with botulinum toxin alone, 5860 clinical use is well documented. On the basis of premeeting surveys, Figure 1 summarizes the panelists’ use of botulinum toxin alone, combined treatment with fillers, and fillers alone.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Recent comparative studies have established the safety and enhanced efficacy compared with solo treatment of combined treatments for lower face rejuvenation. 1,2 A 2008 North American consensus cited combination treatment as important for the lower face and sometimes appropriate for the upper face. 3 French consensus recommendations in 2011 4,5 and a panel of five experts from Canada, Europe, and South America in 2013 6 affirmed the value of the combined approach.…”
mentioning
confidence: 99%